What about all that “change in journalism studies” fuss? - Leila O. Algavi (RUDN Journal of Studies in Literature and Journalism, 2019)
The article is a critical review of the materials of a special issue of Journalism (SAGE Publications, Q1). The issue devoted to academic research in the fi eld of journalism studies, there are scientists from Denmark, Great Britain, Australia, Canada and other countries among the authors of the special issue.